Developing Pedagogical Standards and AI Policies for Adaptive Learning in Equitable and Safe School Education - Masfufah; Didit Darmawan (Global Action and Education for Society, 2023)
This article discusses the utilization of artificial intelligence in adaptive learning in schools and how advancements in pedagogical standards and regulations can ensure the quality, safety, and social acceptance of the system. The analysis focuses on opportunities, challenges, and strategies for equalizing access to technology, data protection, teacher engagement, and national standard requirements. In the digital age, artificial intelligence is increasingly dominating personalized and data-driven learning models, so schools are expected to be responsive to technological developments and build collaborations with various parties. The importance of digital infrastructure, student data protection, teacher training, and participatory regulations was emphasized. Lack of infrastructure remains a barrier to equitable access, while the professional adaptation of educators is a key to success. Regular regulations, independent audits, data transparency, and the involvement of the school community play a role in maintaining public trust in artificial intelligence systems in education. This transformation must be balanced with a learning culture that is open, fair, and values diversity. The formulation of recommendations includes strengthening infrastructure, developing national standards, increasing digital literacy, and empowering school communities. This study concludes that equal access and the implementation of robust artificial intelligence pedagogical standards are crucial for delivering quality and sustainable education. Collective consciousness and policy updates must go hand in hand with technological changes to ensure the education system remains relevant and capable of responding to future challenges.